Illocutionary and Perlocutionary Acts on Youtube Videos Employed by Niana Guerrero - Muthiara Chairani; Dedi Sofyan; Mei Hardiah (Journal of English Education and Teaching, 2020)
This research is aimed at finding the illocutionary act types performed by Niana Guerrero in her YouTube videos and the perlocutionary effects performed by the hearers in Niana Guerrero’s YouTube videos. This research employed a qualitative descriptive research. The subjects of this research were two of the most viewed videos uploaded from May 2019-August 2019. After listing, selecting, and collecting the videos, the videos were watched several times to ease the researcher in transcribing them. In analyzing the data, the researcher only took the interactional conversations which enabled Niana to deliver her intentions to the hearers directly and enabled the hearers to fulfill Niana’s intentions directly as well. The illocutionary act data performed by Niana Guerrero were classified using an instrument following Searle’s theory and the perlocutionary effect data performed by the hearers were classified using an instrument following Gu’s theory. The first finding showed four illocutionary act types performed by Niana Guerrero namely representative, directive, commisive, and expressive. The second finding showed all of the six perlocutionary effect types performed by the hearers namely motor reflexive response, emotive response, cognitive response, negative response, verbal response, and physical response. By performing four types of illocutionary acts, Niana Guerrero may have various ways to express her intentions to the hearers. Meanwhile, the hearers may have various ways to fulfill Niana Guerrero’s intention by performing six types of perlocutionary effects. These speech acts create the communicative effects that cause Niana Guerrero having many subscribers and viewers in her YouTube channel by establishing highly interactive, joyful, and interesting situation.